plz answer this question
Attachments:
![](https://hi-static.z-dn.net/files/de4/732e808ee326044633ed1a1d064bdc1b.jpg)
Answers
Answered by
1
Answer:
0
Step-by-step explanation:
By remainder theorem
x^3 + 1 x + 1 = 0 , x = -1
putting value for x
(-1)^3 + 1
= - 1 + 1
= 0
so the remainder is 0
pls mark me the brainliest , rate and say thanks
Answered by
1
Answer:
hope it will help you..
Step-by-step explanation:
Please mark me as Brilliant
Attachments:
![](https://hi-static.z-dn.net/files/db7/a81bede23a41d722bae33aed2285bd47.jpg)
Similar questions